Comparing biological markers of Alzheimer's disease across blood fraction and platforms: Comparing apples to oranges. Issue 1 (29th December 2015) - O'Bryant, Sid E.; Lista, Simone; Rissman, Robert A.; Edwards, Melissa; Zhang, Fan; Hall, James; Zetterberg, Henrik; Lovestone, Simon; Gupta, Veer; Graff‐Radford, Neill; Martins, Ralph; Jeromin, Andreas; et al.
Abstract: Introduction: This study investigated the comparability of potential Alzheimer's disease (AD) biomarkers across blood fractions and assay platforms. Methods: Nonfasting serum and plasma samples from 300 participants (150 AD patients and 150 controls) were analyzed. Proteomic markers were obtained via electrochemiluminescence or Luminex technology. Comparisons were conducted via Pearson correlations. The relative importance of proteins within an AD diagnostic profile was examined using random forest importance plots. Results: On the Meso Scale Discovery multiplex platform, 10 of the 21 markers shared >50% of the variance across blood fractions (serum amyloid A R 2 = 0.99, interleukin (IL)10 R 2 = 0.95, fatty acid‐binding protein (FABP) R 2 = 0.94, I309 R 2 = 0.94, IL‐5 R 2 = 0.94, IL‐6 R 2 = 0.94, eotaxin3 R 2 = 0.91, IL‐18 R 2 = 0.87, soluble tumor necrosis factor receptor 1 R 2 = 0.85, and pancreatic polypeptide R 2 = 0.81). When examining protein concentrations across platforms, only five markers shared >50% of the variance (beta 2 microglobulin R 2 = 0.92, IL‐18 R 2 = 0.80, factor VII R 2 = 0.78, CRP R 2 = 0.74, and FABP R 2 = 0.70). Discussion: The current findings highlight the importance of considering blood fractions and assay platforms when searching for AD relevant biomarkers.